Frequency of Canal Configuration in Maxillary First Premolars and Mandibular Second Premolars - M - Hasheminia; A Hashemi (Isfahan University of Medical Sciences, 2006)
Introduction: The human teeth have many anatomical variations and treatment of each tooth is under the influence of its configuration. Therefore, recognizing canal configuration is necessary for a correct endo-dontic therapy, and lack of information about canal configuration causes failure in therapy. Since one of the most effective factors on canal configuration is race, we planed to have an In vitro research in the city of the Isfahan.Methods and Materials: This study was descriptive, and was done on 160 extracted maxillary first premolars and mandibular second premolars, which were collected from a number of clinics and private offices in Isfahan. Teeth were decalicfied, injectetd with dye, and made transparent to determine the number of root canals and their type. Finally, the teeth were cut in cross sections in three points of the root and canal configurations of teeth were evaluated. The specimens were classified according to Weine system by naked eye.Results: In clearing Method, from 80 total sample sizes, most of them were type III (67.5 percent). Mandibular second premolars, from 80 total sample sizes, most of them were type I (91.25 percent). In sectional methods, from 80 total sample sizes, most of them were type III (70 percent) and frome mandibular second premolars, from 80 total sample sizes, most of them were type I (88/75 percent).Conclusion: In other countries many researches have been done using different methods about internal anatomy of teeth and the results are different form this study. It appears that the differences are due to genetic or race factors and methods used. Additionally, results of different studies indicate that more attention should be given to studies on canal configuration of these teeth.Key words: Root canal configuration, Maxillary first premolar, Mandibular second premolar.